2014
DOI: 10.1186/bf03353019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of peculiar volcanic earthquakes at Satsuma-Iojima volcano

Abstract: Fukuoka District Meteorological Observatory has continued seismic observations at Satsuma-Iojima volcano since September 1997. Of the daily number of seismic events at the volcano, which sometimes exceeded 100, several different types have been observed. Hypocenters of A-type earthquakes mostly existed in a shallow area within the volcanic island. Numerous peculiar earthquakes that have waveforms different from usual volcanic earthquakes were observed with the ascent of seismic activity. They have an emergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 1 publication
(5 reference statements)
3
10
0
2
Order By: Relevance
“…The various flow structures in felsic dykes, as described above, are comparable with those observed in lava (see Fink 1980;Ventura & Vesuviano 1997;Gregg et al 1998;Beam & Fischer 1999;Castro & Cashman 1999;Uchida & Sakai 2002;Tuffen et al 2003;Rust et al 2004;Iezzi & Ventura 2005;Lescinsky & Merle 2005; and references therein), but are different from those observed in magmatic plutons (see Baer 1987;Philpotts & Asher 1994;Williams & Tobisch 1994;Weinberg et al 2001;Paquet et al 2007;and references therein). A simple cause for this comparability is that both must have formed in similar conditions of a fast flow rate and a fast cooling rate.…”
Section: Environmentsupporting
confidence: 59%
See 1 more Smart Citation
“…The various flow structures in felsic dykes, as described above, are comparable with those observed in lava (see Fink 1980;Ventura & Vesuviano 1997;Gregg et al 1998;Beam & Fischer 1999;Castro & Cashman 1999;Uchida & Sakai 2002;Tuffen et al 2003;Rust et al 2004;Iezzi & Ventura 2005;Lescinsky & Merle 2005; and references therein), but are different from those observed in magmatic plutons (see Baer 1987;Philpotts & Asher 1994;Williams & Tobisch 1994;Weinberg et al 2001;Paquet et al 2007;and references therein). A simple cause for this comparability is that both must have formed in similar conditions of a fast flow rate and a fast cooling rate.…”
Section: Environmentsupporting
confidence: 59%
“…They can be observed in magmatic rocks emplaced at variable depth, from lavas to dykes and plutons, but their abundance tends to decrease with increasing depth. For volcanologists, recent interest in lava has concentrated on the analysis of strained bubbles (Uchida & Sakai 2002;Rust et al 2004), deformed porphyroblasts and enclaves (Beam & Fischer 1999;Iezzi and Ventura 2005), buckling or bending of magmatic bands (Ventura & Vesuviano 1997;Castro & Cashman 1999), and brittle-ductile deformation at the contact with the wall rocks (Fink 1980;Gregg et al 1998;Tuffen et al 2003;Lescinsky & Merle 2005), from which lava viscosity, vorticity, strain rate and other kinematic parameters have been estimated or examined. These parameters are fundamental for the characterization of lava flows, and are of practical use in the prediction of hydrothermal deposit formation (Vigneresse 2007) and in the assessment of volcanic hazards (Costa & Macedonio 2005).…”
mentioning
confidence: 99%
“…Although there is a common belief that these earthquakes are intrinsically linked to the flow dynamics of the rising magma, opinions have differed over the past decade as to whether magma-water interaction, stick-slip motion, shear fracture or episodic gas loss is the trigger mechanism (Chouet 1988;White et al 1998;Goto 1999;Hidayat et al 2000;Kumagai and Chouet 2000;Neuberg 2000;Uchida and Sakai 2002;Umakoshi et al 2002). For example, Kumagai and Chouet (2000) have suggested that resonance of cracks containing ash and gas can create seismic signals with the spectral characteristics of observed hybrid and long-period events, whereas Sturton and Neuberg (2003) and Jousset et al (2003) show how the same spectra can be generated by resonance of the entire fluid-filled conduit.…”
Section: Volcano Seismicity and Brittle Magma Deformationmentioning
confidence: 99%
“…Many eruptions, especially prolonged dome-building eruptions with a compositional range between basaltic andesite and rhyolite, are accompanied by repetitive long-period (LP), hybrid and volcano-tectonic (VT) earthquakes with moment magnitudes between 1 and 3, which are thought to originate in a small volume of the volcanic edifice, either in or adjacent to the conduit, at a depth of <2 km (e.g. Lahr et al 1994;Chouet 1996;Stix et al 1997;Gil Cruz and Chouet 1997;White et al 1998;Hidayat et al 2000;Neuberg 2000;Uchida and Sakai 2002;Umakoshi et al 2002Umakoshi et al , 2003. Hybrid and LP events show no S-wave arrivals and the frequency content is mostly restricted in a narrow band between 1 and 3 Hz (e.g.…”
Section: Volcano Seismicity and Brittle Magma Deformationmentioning
confidence: 99%
“…Fukuoka District Meteorological Observatory (FDMO) installed seismic stations around Mt. Iwodake temporarily, and the signals are transmitted to FDMO by using radio and telephone lines (Uchida and Sakai, 2002). The station JMA has been installed for long-term monitoring ( Fig.…”
Section: Observationsmentioning
confidence: 99%